2022
DOI: 10.3390/su14041972
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Customer Intentions to Use Electric Vehicle in Indonesia: An Integrated Model Analysis

Abstract: Electric vehicles can be a solution to certain social problems in Indonesia, such as pollution and an increase in consumption of energy from fossil fuels, which cannot be met by domestic production. The discussion of the TPB theoretical model, UTAUT2, and risk perception, using the structural equation modeling (SEM) method, in this study aims to provide an overview of the factors that drive interest in adopting electric vehicles in Indonesia. Data were collected from 526 respondents in various cities located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 70 publications
(166 reference statements)
3
13
0
Order By: Relevance
“…The effect of PU and PEOU on BI was consistent with the findings of previous studies (Panagiotopoulos and Dimitrakopoulos 2018;Liu et al 2019;Zhang et al 2021). The influence relationships of PBC, BA, and SN with BI were also consistent with previous studies (Buckley et al 2018;Acheampong and Cugurullo 2019;Gunawan et al 2022). Moreover, it was concluded that HMRP indirectly influences the acceptance of AVs through PBC and BA, and HMRP on acceptance of AVs has a significant negative influence relationship.…”
Section: Path Analysis and Verification Of Structural Equation Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of PU and PEOU on BI was consistent with the findings of previous studies (Panagiotopoulos and Dimitrakopoulos 2018;Liu et al 2019;Zhang et al 2021). The influence relationships of PBC, BA, and SN with BI were also consistent with previous studies (Buckley et al 2018;Acheampong and Cugurullo 2019;Gunawan et al 2022). Moreover, it was concluded that HMRP indirectly influences the acceptance of AVs through PBC and BA, and HMRP on acceptance of AVs has a significant negative influence relationship.…”
Section: Path Analysis and Verification Of Structural Equation Modelsupporting
confidence: 91%
“…TPB has been found to be able to explain, predict, and intervene in the occurrence of a phenomenon through the relationship between behavioral intention and actual behavior (Shalender and Sharma 2021). In addition, the validity of applying TPB to explain the process of external factors influencing the acceptance of AVs is supported by many previous studies (Rahman et al 2017;Buckley et al 2018;Acheampong and Cugurullo 2019;Gunawan et al 2022).…”
Section: Constructs From Technology Acceptance Model and Theory Of Pl...mentioning
confidence: 80%
“…When viewed on the market, the price of environmentally friendly goods is often more premium when compared to products that are not/less environmentally friendly. Research conducted in Pakistan shows that consumers tend to choose environmentally friendly products when they have a higher quality compared to conventional products [11]. Research conducted with European and non-European tourist respondents showed that the value of the function represented by price was significantly positive with green purchase intention [12].…”
Section: Theory Of Consumptionmentioning
confidence: 99%
“…Prasetio et al [4] indicated that Indonesian are mainly sensitive to travel time and congestion when selecting their transportation mode. Gunawan et al [5] suggested that the attitude toward use (ATU) factor by effort expectancies and performance, price value, hedonic motivation, operational, social, and financial risks influence EVs in Indonesia. The results indicate that only financial risk factors and perceived operational break customer intentions to use EVs.…”
Section: Introductionmentioning
confidence: 99%